Mycoflora and Total Aflatoxin Isolated from Dry Dates in Sana'a, Yemen - Shatar, Abdul-Rahman M.; Alghalibi, Saeed M.; Al-Zubairy, Maysoon A. (Thamar University Journal of Natural & Applied Sciences, 2023)
This study is designed to record the mycoflora and total aflatoxin isolated from dry dates in Yemen Republic. Thirty four date samples collected from different shops and markets in Sana’a city were analyzed mycologically for the presence of fungi cultivated on three types of media. Eight species belonging to 7 genera were isolated from analyzed date samples on the three cultural media. Aspergillusgenera was the most dominant fungi and grew well on the three type of media of which A. niger is the most common species, A. flavus was isolated in rare, low and rare frequency on 1% and 20% sucrose Czapek’s and Sabouraud dextrose agar media. Rhizopus stolonifer was isolated in rare, low and low frequency on 1, and 20% sucrose Czapek's and Sabouraud dextrose agar media. The date samples were analyzed for the presence of total aflatoxin using ELISA technique which revealed that 4 out of 5 date samples were contaminated with aflatoxin ranged from 3059.89-7585.96 ppt (ng Kg-1).